2018
DOI: 10.17116/neiro201882329
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic models of the severity of acute dynamic pain on the first postoperative day and the likelihood of chronic postoperative pain in spine surgery

Abstract: The developed software in the form of MS Excel calculators provides a particular patient with preoperative assessment of the risk for minor acute dynamic pain on the 1 postoperative day and CPS 5-7 months after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
1
Order By: Relevance
“…Interestingly, our analysis revealed that lower age was significantly associated with worse COMI outcomes after 3 weeks postoperatively. This is contrary to other findings which show no significant association [ 36 ] or an inverse association between age and PROMs after spine surgery 51–54 [ 37 , 38 , 39 , 40 ]. However, our data is in accordance with the findings of one of the largest predictive studies in spine surgery, involving 15 hospitals and 1965 surgical patients [ 41 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, our analysis revealed that lower age was significantly associated with worse COMI outcomes after 3 weeks postoperatively. This is contrary to other findings which show no significant association [ 36 ] or an inverse association between age and PROMs after spine surgery 51–54 [ 37 , 38 , 39 , 40 ]. However, our data is in accordance with the findings of one of the largest predictive studies in spine surgery, involving 15 hospitals and 1965 surgical patients [ 41 ].…”
Section: Discussioncontrasting
confidence: 99%
“…We included studies in patients undergoing cervical spine (n = 3), thoracolumbar spine (n = 2), and lumbar spine (n = 8) surgery [3••, 5••, 6••, [23][24][25][26][27][28][29][30][31][32]. These studies reported predictive models (n = total number of models) to estimate post-surgical patient-reported outcomes of the following: return to work (n = 3), pain (n = 9), physical functioning and disability (n = 5), quality of life (QOL) (n = 6), and psychosocial disposition (n = 2) reported in Table 4.…”
Section: Predicted Patient-reported Outcomes By Spine Regionmentioning
confidence: 99%